One-stage surgical treatment of neglected simultaneous bilateral locked posterior dislocation of shoulder: a case report and literature review - Elmali, NURZAT; ELMALI, NURZAT; TASDEMIR, Zeki; SAGLAM, Fevzi; GULABI, Deniz; BAYSAL, Ozgur (My University, 2015)
Simultaneous bilateral locked posterior dislocation of the shoulder is a rare injury. Herein, we present a 59-year-old male case with a three-month history of an irreducible locked bilateral posterior dislocation of the shoulders with an associated large impression fracture on the anteromedial aspect of both humeral heads after a grand mal type epileptic seizure. Plain X-ray and computed tomograph revealed a defect on the right side more than 40% of the articular surface, and on the left side, 30%. He was treated with a one-stage operation with a reconstruction of femoral head osteochondral allograft on the right side and transfer of the osteotomized tuberculum minus with its attached subscapularis tendon into the defect (modified McLaughlin technique) on the left side. At 14 months during follow-up, the patient was pain-free with stable shoulder joints and satisfactory functionality.